2016
DOI: 10.3390/ijms17040522
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Differentially Induces Inflammatory and Metabolic Gene Expression in the Adipose Tissues of Lean and Obese Mice

Abstract: The functions of interleukin-17A (IL-17A) in adipose tissues and adipocytes have not been well understood. In the present study, male mice were fed with a regular diet (n = 6, lean mice) or a high-fat diet (n = 6, obese mice) for 30 weeks. Subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) were analyzed for IL-17A levels. SAT and VAT were treated with IL-17A and analyzed for inflammatory and metabolic gene expression. Mouse 3T3-L1 pre-adipocytes were differentiated into adipocytes, followed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…In our study, the M1 macrophages infiltration is associated with IL-17 overexpression in gWAT. This finding is concordant with studies showing tight correlation between IL-17 inflammation in WAT and obesity 44 , 45 . All these results confirm the obesogenic effect of perinatal exposure to BPA in offspring mice, with close characteristics to human obese phenotype, hence validate our in vivo model to study the chronological development of immune and gut microbiota imbalance associated with this phenotype.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the M1 macrophages infiltration is associated with IL-17 overexpression in gWAT. This finding is concordant with studies showing tight correlation between IL-17 inflammation in WAT and obesity 44 , 45 . All these results confirm the obesogenic effect of perinatal exposure to BPA in offspring mice, with close characteristics to human obese phenotype, hence validate our in vivo model to study the chronological development of immune and gut microbiota imbalance associated with this phenotype.…”
Section: Discussionsupporting
confidence: 92%
“…The secretion of IL-17A was found to be more active in salt-loading adipocytes. Qu et al has shown that increased expression of IL-17A also increases the expression of metabolic genes [45]. It has also been reported that paracrine agents released by high salt cause changes in the lipogenesis and lipolysis of adipose tissues by recruiting macrophages and T helper cells [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that IL-17A is an important pro-inflammatory cytokine which prompts macrophages, T cells and epithelial cells to produce and release other chemokines or cytokines to mediate tissue infiltration, inflammation, destruction and remodeling [15, 16]. Thus, IL-17A exerts various functions, and has been implicated in several disease models [2628]. Previous work from our laboratory demonstrated epidermal IL-17A production is increased after skin injury, and the administration of IL-17A neutralizing antibody on wound beds significantly improved wound healing [29].…”
Section: Discussionmentioning
confidence: 99%